Factors affecting employee turnover in organization / Nur Zuhan Munauwarah Omar Ali - Omar Ali, Nur Zuhan Munauwarah (Faculty of Business and Management, 2017)
The purpose of this study was to find the factors affecting employee turnover in organizations. Employee turnover is one of the problems faced by organizations and make them worried. Turnover causes the performance of an organization to decrease, loss of momentum, distrupt the production and allocation of duties, and also incurs additional costs that impact the organization. The research objectives are to measure the level of salary, benefits, work life balance and recognition with employee turnover, to examine the relationship between salary, benefits, work life balance and recognition with employee turnover, and lastly is to determine the significant predictor variable of employee turnover in organization. 108 questionnaires were distributed conveniently and the data were analyzed by using Statistical Package of Social Science (SPSS) for descriptive analysis, reliability analysis, correlation and multiple regression analysis. All of the questions hang well together as a set, and all of the independent variables which are salary, benefits, work life balance and recognition are significant and have positive relationship with employee turnover. These findings answered all of the research questions. This research would benefit the organization as well as future researches.